Evaluasi penerapan produksi bersih pada UMKM tempe di Kelurahan Guntung Paikat, Banjarbaru, Kalimantan Selatan - Novianti Adi Rohmanna; Nelva Kamila Syahnazia; Andira Mawardani; Nur Sabrina; Nurul Fayzhatun Nisa; Septiana Nurmala (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Tempe is a product that the people of Indonesia popularity, mainly South Kalimantan. The increase in tempeh production in MSMEs in Banjarbaru is proportional to the demand. It has an impact on increasing waste production. Currently, environmental issues are one of the urgent topics for MSMEs, including Tempe MSMEs. Therefore, it is necessary to carry out a clean production analysis. This study aims to evaluate the application of cleaner production in the Tempe industry. Activities were carried out at MSMEs ABC in Guntung Paikat, Banjarbaru City, South Kalimantan. The method used is quick scanning at all stages of the process. The activities begin with identifying production processes, identifying clean production opportunities, determining priority scales, and feasibility studies for implementing clean production. The study shows that wastewater is the most produced from Tempe production. Based on determining the priority scale, applying multilevel filtration technology is a choice for reducing water usage and minimizing liquid waste. The feasibility calculations show that the application of this technology has a PP value of 15 months.